(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The Sellout’ is a fictional novel, a satirical commentary on race relations in America. The wholestory of this novel makes social commentary on stereotypes. Like Paul’s other works, this novel is alsohumorous, but it is also true that Paul does not consider himself a satirical writer. The Sellout waspublished in 2015 by Farrar, Strauss and Giroux, Oneworld Publications (a United Kingdom’spublication). ’The Sellout’ received the ’National Book Critics Circle Award (Fiction) in 2016, while thisnovel also won the Booker Prize in 2016. This book was traditionally the first American book to win the’Booker Prize’. Ostensibly, Slumberland, Beatty’s third novel, seeks to debunk such monolithic andmonotonous racial myth-making. Slumberland is a story of stereotypes abused and archetypesreclaimed which delights in racial essentialism even as it decries it and dismisses hipness using thehippest touchstones Beatty can lay his hands on.